1999
DOI: 10.2108/zsj.16.693
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific Variation of Mitochondrial CytochromebGene Sequences of the Japanese Marten Martes melampus and the Sable Martes zibellina (Mustelidae, Carnivora, Mammalia) in Japan

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
21
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 13 publications
6
21
0
Order By: Relevance
“…In the lineages of Martes melampus, for example, populations of Honshu and the Tsushima Islands possessed different haplotypes (Fig. 2), as was documented by Kurose et al (1999a) and Hosoda et al (1999).…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…In the lineages of Martes melampus, for example, populations of Honshu and the Tsushima Islands possessed different haplotypes (Fig. 2), as was documented by Kurose et al (1999a) and Hosoda et al (1999).…”
Section: Resultsmentioning
confidence: 72%
“…A knowledge of the molecular phylogeny of the group of Mustelidae is being accumulated with analyses of DNA-DNA hybridization (Wayne et al, 1989), mitochondrial DNA (mtDNA; Yoshida,1994a, 1994b;Carr and Hicks, 1995;Ledje and Arnason, 1996;Hosoda et al,1997Hosoda et al, ,1999Koepfli and Wayne, 1998;Demboski et al, 1999;Kurose et al, 1999aKurose et al, , 1999bKurose et al, , 2000 and the nuclear ribosomal RNA gene spacers (Hosoda et al,1993) but a comprehensive view of the molecular evolution is still to be achieved. Here we analyzed intra-and inter-specific variation in the mitochondrial cytochrome b (cyt b) gene sequences in several species of the mustelid, especially those of Martes and Mustela.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies revealed that M. zibellina is distributed widely in central, eastern and northern Hokkaido (Murakami and Ohtaishi 2000). The mitochondrial DNA (mtDNA) phylogenetic studies on the Japanese M. zibellina have also been done by some researchers (Hosoda et al 1999;Kurose et al 1999;Murakami et al 2004). Kurose et al (1999) analyzed the mtDNA cytochrome b gene, and reported that the genetic variation of M. zibellina on Hokkaido is relatively smaller, and it has no clear geographic structures.…”
mentioning
confidence: 99%
“…Together with previously determined homologous gene sequences (Kurose et al 1999 gene. In total, 59 sables from Russia (n = 35) and Hokkaido (n = 24) were analyzed.…”
Section: Cytb Sequence Variationmentioning
confidence: 99%
“…Therefore, it is possible that the two martens on Hokkaido hybridise in the contact zone between their current distributions. With one exception (Murakami et al, 2004), genetic analyses have found no sign of hybridisations between them (Hosoda et al 1999;Kurose et al 1999;Sugimoto et al 2009;Inoue et al 2010). …”
Section: Introductionmentioning
confidence: 99%